The Role of Strategic Reference Points in Explaining the Nature and Consequences of Human Resource Strategy - Bamberger, Peter; Fiegenbaum, Avi (Academy of Management Review, 1996)
Peter Bamberger, Avi Fiegenbaum, The Role of Strategic Reference Points in Explaining the Nature and Consequences of Human Resource Strategy, The Academy of Management Review, Vol. 21, No. 4 (Oct., 1996), pp. 926-958